PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATA KULIAH TATA HIDANG - Haryanto, Haryanto; Mulyatiningsih, Endang; E, Prihastuti (Universitas Negeri Yogyakarta, 2005)
The goal of this research in research & design on technology is to produce video learning media prototype needed for